The impact of WSARA on the cost of air force weapon systems. Issue 1 (4th March 2019) - Ritschel, Jonathan D.; Lucas, Brandon; White, Edward; Mrla, Danielle
Abstract : Purpose: The Weapon Systems Acquisition Reform Act (WSARA) was enacted in 2009 to improve Department of Defense public procurement processes and limit cost overruns in major acquisition programs. Design/methodology/approach: Seven years later, the authors investigate the effects of WSARA on cost overruns for major Air Force acquisition programs and then conduct an exploratory case study specifically targeting WSARA impacts on the Operations and Support phase of a program's life cycle. Findings: The authors find that while there are some positive impacts on cost overruns in limited areas, the majority of the models demonstrate either no statistically significant effect from WSARA or an increase in cost overruns post implementation. Originality/value: These findings are consistent with much of the literature on the historical ineffectiveness of previous acquisition reforms to ameliorate cost overruns.